In-Situ Transesterification of Biodiesel from Jatropha Curcas - Ginting, M S Abadi (2008)
Biodiesel is a renewable fuel made up from a chemical reaction of alcohol and vegetable or animal oils, fats or greases. High feedstock and processing cost are the main drawback that hindered the biodiesel production currently. The use of non-edible oil, for instance jatropha curcas, can reduce the high feedstock cost since it does not compete with food and this lead to a cheaper feedstock source.Besides, we hoped that these problems can be counterbalanced by combining both extraction and reaction steps (in situ transesterification). Thin Layer Chromatography (TLC) and Gas Chromatography (GC) were used to analyse the liquid product i.e alkyl ester. We studied the effect of different types of base catalyst (NaOH and KOH) and their concentration for instances 0.5, 1.0, 1.5 and 2.0 (wt %), reaction time (2, 4 and 6 hours) and types of alcohol (methanol and ethanol). We produced the highest yield of the alkyl ester (99.97%) at 30°C, with 2.00 wt % sodium hydroxide (NaOH) concentration and 6 hours reaction time.